Energy Efficient Joint Power Control and User Association Optimization in Massive MIMO Enabled HetNets - Liangrui Tang; Hailin Hu; Yanhua He (Applied Sciences, 2018)
Massive MIMO enabled heterogeneous cellular networks (HetNets) have a wide application prospect in improving end-to-end performance. To increase the performance of energy efficiency (EE), we formulate the joint optimization problem of power control and user association in this paper. Unfortunately, the problem is a fractional and mixed integer nonlinear programming problem (FMINLP). Nevertheless, an energy efficient joint power control and user association optimization algorithm is proposed to solve the problem. Firstly, based on the Dinkelbach’s theorem, we transform the objective function of the problem into an integral expression and propose the optimal EE iterative algorithm. Then, with the help of the approximately iterative method and Lagrange’s decomposition dual method, the problem can be transformed into a convex optimization problem and the joint optimization algorithm is proposed correspondingly. In the simulation, the performance of EE and its influence factors are analyzed and some interesting points are discussed.